1999
DOI: 10.4102/jsava.v70i4.783
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an angiotensin-converting enzyme inhibitor on water and electrolyte balance in water-restricted sheep

Abstract: The importance of angiotensin II in the regulation of water and electrolyte balance in sheep is questionable. In this trial the effects of an angiotensin-converting enzyme (ACE) inhibitor were quantified in sheep on restricted water intake. Comparing the phase of water restriction only with that of water restriction plus ACE inhibition, significant increases were observed during the latter phase in urine volume, sodium and potassium excretion <em>via</em> the urine, sodium concentration in the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The finding that both an inhibitor of Ang II synthesis and an AT 1 R antagonist prevented the ovariectomy-induced decrease in the FE K+ supports this hypothesis. Furthermore, previous studies have shown that blocking AT 1 Rs or inhibiting Ang II action decreases plasma potassium by increasing potassium excretion (2,15,20).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that both an inhibitor of Ang II synthesis and an AT 1 R antagonist prevented the ovariectomy-induced decrease in the FE K+ supports this hypothesis. Furthermore, previous studies have shown that blocking AT 1 Rs or inhibiting Ang II action decreases plasma potassium by increasing potassium excretion (2,15,20).…”
Section: Discussionmentioning
confidence: 99%
“…The significant (p < 0.05) increase in serum urea concentration in the experimental animals under 40% water restriction is attributed to haematic concentration of metabolites that leads to the inability of the kidney to perform its function (Casamassima et al, 2016). It may also partially be related with increase in secretion of hormone angiotensin and vasopressin which are released from neurohypophysis in response to dehydration and increase permeability of collecting ducts of kidneys and thereby promote urea reabsorption in the kidneys and reduce loss of urea concentration (Meintjes and Engelbrecht, 1999). In earlier studies also, the water deprivation was associated with significant (p < 0.05) increase in serum urea concentration (Alamer, 2006;Hamadeh et al, 2006;Abdelatif et al, 2010;Gupta, 2013;Khanvilkar et al 2017 b ).…”
Section: Results a N D Discussionmentioning
confidence: 98%
“…collecting duct of kidneys and there by promote urea reabsorption in the kidneys and reduced the loss of urea concentration (Meintjes and Engelbrecht, 1999). The cortisol could be a good indicator in accessing acute stress response in small ruminants but not chronic stress such as dehydration, also reported that, cortisol level did not return to normal level even after 72 hours of rehydration (El-Nouty et al, 1991).…”
Section: Issn: 2319-7706 Volume 9 Number 6 (2020)mentioning
confidence: 99%